2022
DOI: 10.25011/cim.v45i3.38933
|View full text |Cite
|
Sign up to set email alerts
|

KMT5A Knockdown Suppresses Osteosarcoma Cell Proliferation and Metastasis Through Ꞵ-Catenin Signalling

Abstract: Purpose: Osteosarcoma (OS) is the most common malignant solid bone tumor in children and young adults. We aimed to investigate the effects and cellular mechanisms of KMT5A on OS cell activity.Methods: The protein expression was evaluated in the clinical normal, adjacent and OS osteogenic tissues. Knockdown of KMT5A was achieved by KMT5A siRNAs in a human OS cell line, MG63, to detect cell proliferation and metastasis.Results: KMT5A expression was upregulated in clinical OS tissues. Knockdown of KMT5A inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…2B). Furthermore, we compared the expression of three genes that have been demonstrated in other studies to be associated with lung metastasis in OS [13][14][15]. The results indicate high expression of these genes in MLN and PT (all p < 0.05, Wilcoxon test), suggesting that these genes may also be involved in the LN metastasis (Fig.…”
Section: Transcriptional Characteristics Of Osteoblast Cells During T...mentioning
confidence: 77%
“…2B). Furthermore, we compared the expression of three genes that have been demonstrated in other studies to be associated with lung metastasis in OS [13][14][15]. The results indicate high expression of these genes in MLN and PT (all p < 0.05, Wilcoxon test), suggesting that these genes may also be involved in the LN metastasis (Fig.…”
Section: Transcriptional Characteristics Of Osteoblast Cells During T...mentioning
confidence: 77%
“…In addition, the ectopic expression of miR-335 or the deletion of its target gene KMT5A can enhance the sensitivity of paclitaxel-resistant breast cancer cells to paclitaxel [22]. Similarly, An et al [23] found that KMT5A promotes the expression of downstream molecules by activating the β-catenin signaling pathway, thereby increasing the proliferation and metastasis of osteosarcoma cells. In our previous studies, we discovered that LINC00473 down-regulates miR-502-3p and up-regulates KMT5A through the ceRNA mechanism, thereby regulating the cell cycle through the LINC00473/miR-502-3p/KMT5A signaling axis, and affecting the proliferation and invasion of pituitary adenomas [15].…”
Section: Discussionmentioning
confidence: 99%